2011
DOI: 10.19030/jabr.v20i3.2212
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents And Consequences Of Job Satisfaction: Testing A Comprehensive Model Using Integrated Methodology

Abstract: This study examines the key antecedents and two important consequences of job satisfaction in a com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 75 publications
0
18
0
1
Order By: Relevance
“…These relationships are supported by some previous researches of ref. [13] and [53], as they also agreed that the nature of the job, the employee relationship with management, and compensation and benefits positively affected employee job satisfaction. Moreover, in the study of ref.…”
Section: A Discussionmentioning
confidence: 97%
“…These relationships are supported by some previous researches of ref. [13] and [53], as they also agreed that the nature of the job, the employee relationship with management, and compensation and benefits positively affected employee job satisfaction. Moreover, in the study of ref.…”
Section: A Discussionmentioning
confidence: 97%
“…They do not require much to make themselves satisfied. Researchers found that social factors have a significant influence over employees" job satisfaction (Baker, 2004). In this study, several social and personal factors are investigated to see the relationship of this factor on employee job satisfaction.…”
Section: Variables Of Job Satisfaction / Dissatisfactionmentioning
confidence: 99%
“…A combined task characteristics model and social information processing model by Griffin et al (1987) proposed that job enrichment and social cues combine to influence perceptions and attitudes. Based on these theories, it is seen that the characteristics of predictors of job satisfaction are very rich, and include role ambiguity, role conflict, motivation, need for achievement, initiating structure, salary, security, relationships, leadership, tasks, working conditions, feedback, job variety, burn out, socialisation and autonomy (Tomaževič et al, 2014;Baker, 2011;Yang, 2010;Igbaria and Guimaraes, 1993).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…The positive outcomes include organisational commitment (Yang, 2010) and performance (Ziegler et al, 2012). The negative outcomes include turnover intention, absenteeism, and horizontal violence (Purpora and Blegen, 2015;Baker, 2011;Yang, 2010;Igbaria and Guimaraes, 1993).…”
Section: Job Satisfactionmentioning
confidence: 99%